1999
DOI: 10.1038/sj.bjc.6690063
|View full text |Cite
|
Sign up to set email alerts
|

Role of thrombin receptor in breast cancer invasiveness

Abstract: The major cause of mortality in breast cancer is the progression of metastatic disease. Although loss of oestrogen receptors (ER) and progesterone receptors is associated with more aggressive disease, 30% of patients with receptor-positive, node-negative tumours develop metastases (Price et al, 1997). A component of the metastatic process is invasion, which is accomplished when the cells can transit the extracellular matrix (ECM) layer. More accurate prognoses might be possible if factors could be identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 34 publications
4
86
0
Order By: Relevance
“…Expression of the thrombin receptor has been detected in human carcinoma cell lines including colon adenocarcinoma (Wojtukiewicz et al, 1995), laryngeal (Kaufmann et al, 1997), breast (EvenRam et al, 1998;Henrikson et al, 1999), pancreatic (Rudroff et al, 1998), and oral squamous cell carcinoma (Liu et al, 2001). We have demonstrated that the metastatic melanoma cells A375SM and WM266-4 overexpress the thrombin receptor (Figure 1).…”
Section: Role Of the Thrombin Receptor In Melanomamentioning
confidence: 87%
See 1 more Smart Citation
“…Expression of the thrombin receptor has been detected in human carcinoma cell lines including colon adenocarcinoma (Wojtukiewicz et al, 1995), laryngeal (Kaufmann et al, 1997), breast (EvenRam et al, 1998;Henrikson et al, 1999), pancreatic (Rudroff et al, 1998), and oral squamous cell carcinoma (Liu et al, 2001). We have demonstrated that the metastatic melanoma cells A375SM and WM266-4 overexpress the thrombin receptor (Figure 1).…”
Section: Role Of the Thrombin Receptor In Melanomamentioning
confidence: 87%
“…The thrombin receptor has recently been implicated to play a central role in tumorigenesis and metastasis (Even-Ram et al, 1998;Nierodzik et al, 1998;Henrikson et al, 1999). Expression of the thrombin receptor has been detected in human carcinoma cell lines including colon adenocarcinoma (Wojtukiewicz et al, 1995), laryngeal (Kaufmann et al, 1997), breast (EvenRam et al, 1998;Henrikson et al, 1999), pancreatic (Rudroff et al, 1998), and oral squamous cell carcinoma (Liu et al, 2001).…”
Section: Role Of the Thrombin Receptor In Melanomamentioning
confidence: 99%
“…In the presence of PAR-1 blocking antibodies, the effects of APC were attenuated. To verify that the PAR-1 blocking antibodies were properly blocking the binding of the protease to the receptor, cells were also treated with 5 nM α-IIa, a known ligand of the PAR-1 receptor that will affect migration of the MDA-MB-231 through its activation [37][38][39]. α-IIa alone or α-IIa with control IgG increased chemotaxis approximately 150%, and this increase was attenuated in the presence of the PAR-1 blocking antibodies.…”
Section: Apc Interaction With Par-1 Is Also Necessary To Increase Chementioning
confidence: 99%
“…7 PAR1 and PAR2 are important in tumor cell motility in melanoma 23,24 and PAR1 is involved in the invasive and metastatic processes of breast, 25,26 ovarian, 6 and pancreatic cancer. 27 PAR1 also has been identified as an oncogene in the transformation of NIH3T3 mouse fibroblasts 28,29 and ectopic expression of PAR1 confers tumorigenicity in PAR1-null breast carcinoma cells.…”
mentioning
confidence: 99%